2020
DOI: 10.14710/jitaa.45.4.261-267
|View full text |Cite
|
Sign up to set email alerts
|

Influences of bull age and season on sperm motility, sperm concentration, and ejaculate volume of Ongole Grade cattle in Singosari National Artificial Insemination Center

Abstract: Ongole Grade cattle is one of local cattle in Indonesia.This study was aimed to analyze the effect of bull age and season on semen quality of Ongole Grade cattles macroscopically (sperm motility, and sperm concentration) and microscopically (semen ejaculate volume) to support the policy and management on improvement of semen production. Data were collected from 533 ejaculates of 10 bulls aged 3, 4, and 5 yr at Singosari National Artificial Insemination Center(SNAIC). The 4-year-old bulls hadhighestsperm motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…FSM in this study tends to increase as increasing age of bulls in each species. Although the optimal point of sperm motility value has not been found in this study, several previous studies reported that the age factor had a significant effect on sperm motility (Boujenane & Boussaq, 2013;Sitanggang, 2018;Suyadi et al, 2020). The effect of seasons on FSM was consistent with previous studies on Simmental Bulls (Hapsari et al, 2022), Limousine Bulls (Konenda et al, 2020), Thapkar Bulls (Perumal et al, 2017), and Karan Fries Bulls (Bhakat et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…FSM in this study tends to increase as increasing age of bulls in each species. Although the optimal point of sperm motility value has not been found in this study, several previous studies reported that the age factor had a significant effect on sperm motility (Boujenane & Boussaq, 2013;Sitanggang, 2018;Suyadi et al, 2020). The effect of seasons on FSM was consistent with previous studies on Simmental Bulls (Hapsari et al, 2022), Limousine Bulls (Konenda et al, 2020), Thapkar Bulls (Perumal et al, 2017), and Karan Fries Bulls (Bhakat et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…This research determined the individual motility value of 70 -75% to test the success of diluent trisaminomethane -egg yolk with the addition of genistein. Suyadi et al (2020) the motility of OG bull reached 67.43%. Spermatozoa concentration is the number of spermatozoa contained in one ml of semen.…”
Section: Discussionmentioning
confidence: 91%
“…Semen high quality is the basic factor that determines the success of the Artficial Insemination (AI) program because semen has an influence on the dimensions of success for pregnant cows and contributes genetically to the offspring produced. In addition to the amount of semen that can be produced by a bull which includes the amount or volume of production per year (Suyadi et al, 2020), consistency of production throughout the year or season (Nugraha et al, 2021), the quality of semen is very important to be used as a criterion in determining the quality of semen for determine the success of livestock genetic quality improvement programs through artificial insemination (Söderquist et al, 1996;Muthiapriani et al, 2019;Novianti et al, 2020).…”
Section: Effect Of Genistein Supplementation In Tris-aminomethane Bas...mentioning
confidence: 99%
“…Numerous variables, such as the season [3], feed [4], age [5], body weight [6], and breed [7], have an impact on the quality of the semen. The quality of the sperm in frozen semen is also impacted by the freezing process.…”
Section: Introductionmentioning
confidence: 99%